Board dynamics - Stiles, Philip (Cambridge : Cambridge University Press, 2021)
Boards of directors are at the apex of organisational decision-making and so are central in ensuring effective corporate governance. But boards are under increasing scrutiny due to the continuing prevalence of scandals and failures. Boards have been viewed as set up to fail because the demands placed upon them cannot effectively be delivered. In this Element, I examine this tension and look at the board as a working group, one which has an input, a process and an output. Through looking at the board as a group, the dynamics of how boards, and the potential for effective and ineffective operation, are highlighted. I conclude with outlining how the future of board dynamics may evolve.
Title from publisher's bibliographic system (viewed on 23 Jun 2021).
Keywords: Boards of directors; Corporate governance